Stereotip Masyarakat Asli Kao Terhadap Pendatang Trans Jawa ( Studi Komunikasi Antar Budaya di Desa Toliwang Kecamatan Kao Barat Kabupaten Halmahera Utara ) - Bahry, Syaiful; Bailussy, Wahyuni; Simabur, Lisda A.; Kahar, Suyatno; Suwarjito, Suwarjito (LPPM Institut Pendidikan Nusantara Global, 2024)
This research is based on the stereotype of Toliwang people, west Kao district, to the Javanese Immigrants. But lack of information or knowledge, so the word